Strong Host Modulation of Rhizosphere‐to‐Endosphere Microbial Colonisation in Natural Populations of the Pan‐Palaeotropical Keystone Grass Species, Themeda triandra - Riley J. Hodgson; Christian Cando‐Dumancela; Craig Liddicoat; Sunita A. Ramesh; Robert A. Edwards; Martin F. Breed (Ecology and Evolution)
ABSTRACT Soil microbiota can colonise plant roots through a two‐step selection process, involving recruitment of microbiota first from bulk soil into plant rhizospheres, then into root endospheres. This process is poorly understood in all but a few model species (e.g., Arabidopsis), which is surprising given its fundamental role in plant and soil ecology. Here, we examined the microbial community assembly processes across the rhizospheres and root endospheres in eight natural populations of the pan‐palaeotropical C4 grass, Themeda triandra, in southern Australia. Using a space‐for‐time substitution approach, we assessed whether bacterial root colonisation patterns conformed to the two‐step model and tested whether community assembly was driven more by deterministic or stochastic processes. Our results show that the two‐step selection process shaped bacterial recruitment dynamics across these natural T. triandra populations, and we provide clear evidence that host plants influence microbial assembly via deterministic pressures that produce strong community convergence within endospheres. These findings highlight the central role of host filtering in shaping a conserved ‘core’ endosphere microbiome. However, limited understanding of these endosphere communities constrains efforts to harness these important relationships to, for example, improve plant propagation and revegetation practices.